Venetian Protected Designation of origin wines traceability: Multi-elemental, isotopes and chemometric analysis. (15th March 2023) - Rapa, Mattia; Ferrante, Marco; Rodushkin, Ilia; Paulukat, Cora; Conti, Marcelo Enrique
Highlights: Wine traceability by multi-elemental, isotopes and chemometric analysis is proposed. 219 samples of seven PDOs from the Veneto region were analysed. As, Ca, Cs, δ 11 B and 87 Sr/ 86 Sr were variables that differentiate the PDOs. Cluster analysis, PCA and seven classification methods were applied. A successful traceability tool for four Venetian PDOs wines was reached. Abstract: The traceability and authentication of PDOs wines are important issues for safeguarding their production and distribution systems. This paper evaluated seven Venetian PDO wines, i.e., Amarone, Bardolino, Custoza, Pinot Grigio, Recioto, Soave and Valpolicella . For this purpose, 219 wine samples from the Veneto region were characterised by determining 63 elements and six isotope ratios by HR-ICP-MS and MC-ICP-MS. Chemometric tools highlighted As, Ca, Cs, δ 11 B and 87 Sr/ 86 Sr as the most informative variables to differentiate the PDOs. Seven classification methods, such as Linear Discriminant Analysis, Quadratic Discriminant Analysis, k-Nearest Neighbours, Naïve Bayes, Random Forest, Artificial Neural Networking, and Support Vector Machine were tested and perform a correct classification for Amarone, Bardolino, Pinot Grigio and Recioto PDOs. This paper successfully proposes for the first time advanced traceability tools of seven Venetian PDO by the use of an integrated approach of multi-elemental and isotopes followed by chemometrics analysis.